2017
DOI: 10.3389/fpsyg.2017.01881
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Effect of Emotion Regulation on Minority Stress and Problematic Substance Use in Lesbian, Gay, and Bisexual Individuals

Abstract: Lesbian, gay, and bisexual (LGB) individuals report higher levels of problematic alcohol and substance use than their heterosexual peers. This disparity is linked to the experience of LGB-specific stressors, termed minority stress. Additionally, bisexual individuals show increased rates of psychopathology, including problematic alcohol and substance use, above and beyond lesbian and gay individuals. However, not everyone experiencing minority stress reports increased rates of alcohol and substance misuse. Emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…First, given bisexual women’s experience of multiple marginalization, they may experience a broader array of discriminatory experiences that may impact their ability to attend to internal states. To this end, Rogers et al (2017) found that emotion dysregulation, a construct that conceptually overlaps with interoceptive deficits, was associated with nonsexual experiences of minority stress. Although it should be noted that emotion dysregulation and interoceptive deficits are not one in the same, they are related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, given bisexual women’s experience of multiple marginalization, they may experience a broader array of discriminatory experiences that may impact their ability to attend to internal states. To this end, Rogers et al (2017) found that emotion dysregulation, a construct that conceptually overlaps with interoceptive deficits, was associated with nonsexual experiences of minority stress. Although it should be noted that emotion dysregulation and interoceptive deficits are not one in the same, they are related.…”
Section: Discussionmentioning
confidence: 99%
“…Although it should be noted that emotion dysregulation and interoceptive deficits are not one in the same, they are related. As such, the measure of emotion dysregulation (i.e., Difficulties in Emotion Regulation Scale; Gratz & Roemer, 2004) utilized by Rogers et al (2017) contains a subscale that assesses “lack of emotional awareness” which is core to interoceptive deficits. It is therefore possible that difficulty identifying and responding to internal emotions may be difficult for bisexual women for a number of reasons, and it may be less specific to their experiences of SV and DE.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that survivors of early childhood victimization exhibit poorer emotion regulation skills than their non-maltreated counterparts (D'Andrea, Ford, Stolbach, Spinazzola, & van der Kolk, 2012). The association between exposure to victimization and emotion dysregulation has also been found among LGB adults (Hatzenbuehler, Nolen-Hoeksema, & Dovidio, 2009;Pachankis, Hatzenbuehler, Rendina, Safren, & Parsons, 2015;Rogers et al, 2017). Emotion regulation is a transdiagnostic factor that shapes the development of internalizing and externalizing mental health challenges (Aldao, Gee, De Los Reyes, & Seager, 2016).…”
Section: Emotion Dysregulation and Mental Health Outcomesmentioning
confidence: 99%
“…With regard to SMs, a number of studies have shown that effective emotion regulation processes serve as a buffer against psychological distress resulting from discriminatory experiences ( Feinstein et al, 2012 ; Brewster et al, 2013 ; Velez et al, 2013 ; Szymanski et al, 2014 ; Puckett et al, 2016 ; Kaufman et al, 2017 ). Recent work with SMs has implicated emotion regulation as a key mediator between minority stress and substance misuse in adults ( Rogers et al, 2017 ) and between SM status and symptoms of depression and anxiety in adolescents ( Hatzenbuehler et al, 2008b ). Additionally, stress-related growth was linked to the use of more effective emotion regulation strategies and, thus, fewer internalizing symptoms ( Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%